2000
DOI: 10.1021/bm9900139
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mineral in the Storage of Elastic Energy in Turkey Tendons

Abstract: Mammals elastically store energy in leg and foot tendons during locomotion. In the turkey, much of the force generated by the gastrocnemius muscle is stored as elastic energy during tendon deformation and not within the muscle. During growth, avian tendons mineralize in the portions distal to the muscle and show increased tensile strength and modulus as a result. The purpose of this study was to evaluate the viscoelastic behavior of turkey tendons and self-assembled collagen fiber models to determine the molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(98 citation statements)
references
References 20 publications
5
91
0
Order By: Relevance
“…Results of these studies suggest that the elastic modulus for types I and II collagen appears to be between 7 and 8 GPa in tendon, in the superficial zone of articular cartilage and in self-assembled type I collagen fibers (Silver et al, 2000(Silver et al, 2a-c, 2002. The value of the elastic modulus for collagens in dermis and cardiovascular tissue is somewhat lower due to differences in molecular packing and composition (Silver et al, 2000b(Silver et al, , 2001b. The value for the elastic modulus measured for dermis (4 MPa) is lower, due to the higher tilt angle and a different cross-link pattern (Silver et al, 2001a).…”
Section: Domain Structure Of Fibrillar Collagensmentioning
confidence: 95%
See 1 more Smart Citation
“…Results of these studies suggest that the elastic modulus for types I and II collagen appears to be between 7 and 8 GPa in tendon, in the superficial zone of articular cartilage and in self-assembled type I collagen fibers (Silver et al, 2000(Silver et al, 2a-c, 2002. The value of the elastic modulus for collagens in dermis and cardiovascular tissue is somewhat lower due to differences in molecular packing and composition (Silver et al, 2000b(Silver et al, , 2001b. The value for the elastic modulus measured for dermis (4 MPa) is lower, due to the higher tilt angle and a different cross-link pattern (Silver et al, 2001a).…”
Section: Domain Structure Of Fibrillar Collagensmentioning
confidence: 95%
“…The value for the elastic modulus measured for dermis (4 MPa) is lower, due to the higher tilt angle and a different cross-link pattern (Silver et al, 2001a). The high value of the elastic modulus for tendon, mineralized tendon and superficial zone of articular cartilage suggests that the physiologic role of fibrilforming collagens in many extracellular matrices may be to promote the storage of elastic energy during tensile deformation (Silver et al, 2000a(Silver et al, , 2000b(Silver et al, , 2001a. It has recently been proposed that mineralization is an efficient means for increasing elastic energy storage and transmission in developing turkey tendons (Silver et al, 2000b;2001a).…”
Section: Domain Structure Of Fibrillar Collagensmentioning
confidence: 99%
“…The Young's moduli are comparable to those of dry collagen (1-8 GPa) presented in literature. [14][15][16][17] After cross-linking with glutaraldehyde, an average Young's modulus value of 14.7 6 2.7 GPa from Eq. (3) or 3.8 6 0.8 GPa from Eq.…”
Section: Bending Testsmentioning
confidence: 99%
“…With macro-tensile testing, the data presented in the literature on the modulus of elasticity (Young's modulus) of dry collagen tissue and collagen fibers range from 1 to 8 GPa. [14][15][16][17] Based on Xray diffraction studies, Puxkandl et al reported that the overall strain of the tendon was always larger than the strain in the individual fibrils. 18 In addition, Sasaki and Odajima 19,20 reported different values of Young's modulus by testing collagen molecules, fibrils and tendons.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers focused on the relationship between the fine structure of the periodic banding pattern of type I collagen, the onset and progression of mineralization and elastic strain energy storage during tensile deformation of the protein. [29][30][31] Their works have led to biomechanical considerations of elastic energy storage in collagen and the molecular basis for elastic and viscous deformation, as well as for energy storage of collagen. [32] It is proposed that tensile deformation of collagen involves stretching of the flexible regions in its hole and overlap zones that are opened to provide possible binding sites for calcium and phosphate ions involved in mineralization.…”
Section: Collagen-mineral Interactionsmentioning
confidence: 99%